Fashion Innovation Feasibility Study Celestique Transformabel For Stage Performance App in the Creative Industry - Jannah, Frida Miftaqul; Krisnawati, Maria (Universitas Negeri Semarang, 2026)
Phenomenon appearance singer on stage entertainment featuring two songs with atmosphere different However only use one costume often make appearance fashion no in harmony with nuances song next and reduce strength expression stage. Situation this push idea implementation technique fashion transformable as solution practical for allows change appearance fast without must replace costume in a way overall. Research this aim study eligibility innovation fashion Celestique Transformable as costume show stage in context industry creative. The method used is descriptive quantitative with approach Design Thinking from the Hasso Plattner Institute of Design at Stanford, which includes five stages: empathize, define, ideate, prototype, and test. Evaluation done by three expert design fashion based on six indicators, namely design, size, technique stitching, aesthetics, performance, and features. Research results show that fashion Celestique Transformable assessed worthy used as costume show stage, with notes the need improvements to some technical details to improve performance transformation more optimal and safe for user. Findings This confirm that creation fashion transformable No only produce work innovative, but also expanding outlook about design adaptive costumes to need change appearance as well as potential developed in industry creative.